Sishen Pill Treatment of DSS-Induced Colitis via Regulating Interaction With Inflammatory Dendritic Cells and Gut Microbiota - Chen, Fang; Yin, Yu-Ting; Zhao, Hai-Mei; Wang, Hai-Yan; Zhong, You-Bao; Long, Jian; Liu, Duan-Yong (Frontiers in Physiology, 2020)
Sishen Pill (SSP) is a typical prescription in the pharmacopeia of traditional Chinese medicine, and is usually used to treat inflammatory bowel disease (IBD). In previous studies, we found that SSP alleviated inflammatory symptoms and ameliorated the intestinal barrier function in rats with colitis induced by 2,4,6-trinitrobenzene sulfonic acid. It is known that inflammatory dendritic cells (DCs) and imbalance of gut microbiota play significant roles in the pathogenesis of IBD. However, it is not clear whether SSP can treat IBD by regulating interaction of DCs and gut microbiota. In the present study, the levels of inflammatory DCs and gut microbiota were analyzed by flow cytometry and 16S rDNA analysis. SSP relieved the pathological damage to the colon of mice with colitis induced by dextran sodium sulfate (DSS). As typical indicators of inflammatory DCs, the levels of CD11c+CD103+E-cadherin+ cells and pro-inflammatory cytokines (interleukin-1β, -4, -9 and -17A) were decreased in mice with colitis treated by SSP for 10 days. Simultaneously, the gut microbiota composition was regulated, and beneficial bacteria were increased and pathogenic bacteria reduced. The results indicated that SSP regulated the interaction between inflammatory DCs and gut microbiota to treat DSS-induced colitis.